2008
DOI: 10.1177/1545968307311102
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Sensorimotor Arm Training Mediated by Therapist or Robot Improves Hemiparesis in Patients With Chronic Stroke

Abstract: Investigators have demonstrated that a variety of intensive movement training protocols for persistent upper limb paralysis in patients with chronic stroke (6 months or more after stroke) improve motor outcome. This randomized controlled study determined in patients with upper limb motor impairment after chronic stroke whether movement therapy delivered by a robot or by a therapist using an intensive training protocol was superior. Robotic training (n = 11) and an intensive movement protocol (n = 10) improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
177
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(188 citation statements)
references
References 33 publications
10
177
1
Order By: Relevance
“…In light of prior findings on passive ankle stretching [20][21][22][23] as well as our experience in upper-limb rehabilitation in stroke [26][27][28][29][30][31][32][33], we hypothesized that after 6 wk of anklebot training, the paretic PAS would change in the trained sagittal plane, i.e., DF-PF, but not in the untrained frontal plane, i.e., INV-EV. Moreover, we expected that, to be functionally meaningful, a robotic treatment protocol must emphasize a sequence and timing of sensorimotor stimuli similar to those naturally occurring during gait.…”
Section: Introductionmentioning
confidence: 99%
“…In light of prior findings on passive ankle stretching [20][21][22][23] as well as our experience in upper-limb rehabilitation in stroke [26][27][28][29][30][31][32][33], we hypothesized that after 6 wk of anklebot training, the paretic PAS would change in the trained sagittal plane, i.e., DF-PF, but not in the untrained frontal plane, i.e., INV-EV. Moreover, we expected that, to be functionally meaningful, a robotic treatment protocol must emphasize a sequence and timing of sensorimotor stimuli similar to those naturally occurring during gait.…”
Section: Introductionmentioning
confidence: 99%
“…This plateau is determined by the same problematic clinical tools already discussed. Some authors have suggested that this plateau may actually be the patients consolidating their poststroke practice experience rather than optimal biological recovery [85][86][87] and this, in itself, has important implications in the timing of how we deliver treatment after a stroke.…”
Section: Traditional Approachesmentioning
confidence: 99%
“…Some studies have been criticized for lacking appropriate control groups, because control groups were not present or did not receive an equivalent amount of therapy as the treatment group [104,[112][113]. Other more recent studies have given control subjects an equivalent amount of traditional rehabilitation treatment [85] to control for the confound of differing intensity between control and robotic treatment groups. While we agree that an increased amount of therapy to robotic intervention groups represents a confound in terms of study design, it may actually represent a more real-world scenario then some previous critics have recognized.…”
Section: Use Of Robots For Rehabilitationmentioning
confidence: 99%
“…Disability adds to the costs of disease management that total $74 billion/ year [4]. Developing methods to effectively alleviate residual deficits will reduce health and economic burden of stroke.Several evidence-based rehabilitative approaches have been developed with prominent ones, including neuromuscular electrical stimulation [5], motor learning [6], robotic training [7] constraint-induced movement therapy [8], and bilateral arm training [9], etc. In spite of extensive therapy, recovery is frequently incomplete [10].…”
mentioning
confidence: 99%
“…Several evidence-based rehabilitative approaches have been developed with prominent ones, including neuromuscular electrical stimulation [5], motor learning [6], robotic training [7] constraint-induced movement therapy [8], and bilateral arm training [9], etc. In spite of extensive therapy, recovery is frequently incomplete [10].…”
mentioning
confidence: 99%